Measurement of Arginase Activity in Sera of Iraqi Acromegaly Patients with Diabetes - Fatima Khazaal Malek; Salma Abdul_Rudha Abbas; Baydaa Ahmed Abed (Al-Mustansiriyah Journal of Science, 2024)
The goal of this study was to measure arginase enzyme activity in diabetic acromegaly Iraqi patients and compare it to a control group. This study included 80 participants, whose ages ranged from 25 to 65, and was conducted on forty diabetic acromegaly Iraqi patients attending the national diabetes center of Mustansiriyah University in Baghdad and forty healthy individuals (as a control group). The results showed a highly significant reduction in arginase activity and High-density lipoprotein-cholesterol (HDL-C), Urea levels were reduced not significantly, whereas a highly significant increase in levels of Growth Hormone (GH), Insulin-Like Growth Factor-1 (IGF-1), Fasting Serum glucose (FSG), Total Cholesterol (TC), Triglycerides (TG), Low-density lipoprotein-cholesterol (LDL-C), and Very low-density lipoprotein-cholesterol (VLDL-C)) compared to control. A significant positive correlation was revealed between arginase activity and FSG levels in diabetic acromegaly patients. In conclusion, diabetic acromegaly patients had a significant decreased in serum arginase activity with no significant decrease urea levels, which indicates that their bodies store more nitrogen compounds to be utilized in constructing processes.